Effect of graphene nanoparticles on the histological structure of seminal vesicles of male albino mice - Al-Bairuty, Genan Adnan; AL-kazomy, Asawir Saadi Ali (Iraqi Journal of Science, 2025)
Graphene nanoparticles (GNPs) have drawn a lot of attention recently for their potential use in cutting-edge technology because of their outstanding physical characteristics. Graphene materials’ nanotoxicity, on the other hand, has quickly grown to be a significant issue, particularly in the area of occupational health. Information on the toxicity of GNPs on the male reproductive system accessory gland is lacking. Consequently, this work aims to ascertain how Graphene nanoparticles affected the structure of seminal vesicles in male albino mice. Mice were given 0.1 ml oral gavages containing 10 mg/kg, 20 mg/kg, and 30 mg/kg of GNPs for 14 days. After the end of treatment, seminal vesicles were collected for histological processing. When compared to the controller group, the findings revealed a drop in the mean body weight and seminal vesicle index weight, as well as a reduction in the folded and lined epithelium of seminal vesicles height. As the concentration increased, damage to the seminal vesicles was observed, including a reduction in interstitial tissue, a reduction in fold height, blood vessel congestion, cell shrinkage, and cell destruction. In conclusion, the finding of this study determined that oral GNPs gavages at different concentrations have a detrimental impact on the activity of the male reproductive system.